2016
DOI: 10.3823/2009
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations and hospital cost from cardiovascular diseases in Brazil

Abstract: This study aimed to estimate the number and average cost of hospitalizations from cardiovascular diseases in Brazil. Descriptive, retrospective study with a quantitative approach, on the number and hospitalization cost from cardiovascular diseases (acute myocardial infarction, hypertension and heart failure) in Brazil. The research was conducted by using secondary data, available online at the Department of Health System Information, from 2008 to September 2015. Cardiovascular diseases were responsible for sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…A study carried out in Brazil, the cost of hospitalizations for heart failure and myocardial infarction was estimated to be R$ 3,085.15 per patients which is lower, when compared to this study. (25) Findings of our study is similar to a study which reported a total direct cost of €3198 per patient (1 Euro = 81.69), with largest part of the expenses (79%) attributable to hospitalization (ward), while laboratory investigations and medical treatment accounted for 17% and 4%, respectively. (26)…”
Section: Discussionsupporting
confidence: 88%
“…A study carried out in Brazil, the cost of hospitalizations for heart failure and myocardial infarction was estimated to be R$ 3,085.15 per patients which is lower, when compared to this study. (25) Findings of our study is similar to a study which reported a total direct cost of €3198 per patient (1 Euro = 81.69), with largest part of the expenses (79%) attributable to hospitalization (ward), while laboratory investigations and medical treatment accounted for 17% and 4%, respectively. (26)…”
Section: Discussionsupporting
confidence: 88%
“…Cost of treating CVDs in developed countries appears to be much higher compared to what has been observed in this study. A study carried out in Brazil, the cost of hospitalizations for heart failure and myocardial infarction was estimated to be R$ 3,085.15 per patients which is lower, when compared to this study [ 23 ]. Findings of our study is similar to a study which reported a total direct cost of €3198 per patient (1 Euro = 81.69), with largest part of the expenses (79%) attributable to hospitalization (ward), while laboratory investigations and medical treatment accounted for 17% and 4%, respectively [ 24 ].…”
Section: Discussionmentioning
confidence: 63%
“…This is particularly true for countries such as Brazil, which are transitioning from a healthcare system dominated by communicable diseases to one in which the demands of non-communicable illnesses are emerging. 14 Most previous studies that have attempted to examine the burden of disease in Brazil have been confined to individual diseases in specific regions of the country, 15 , 16 , 17 with no published data on rates of all-cause and cause-specific non-fatal health outcomes nationwide.…”
Section: Introductionmentioning
confidence: 99%